Pt Nanoparticles Confined in a 3D Porous FeNC Matrix as Efficient Catalysts for Rechargeable Li-CO2/O2 Batteries - Zhang, Peng-Fang; Zhuo, Hong-Ying; Dong, Yun-Yun; Zhou, Yao; Li, Yun-Wu; Hao, Hong-Guo; Li, Da-Cheng; Shi, Wen-Jing; Zeng, Su-Yuan; Xu, Shu-Ling; Kong, Xiang-Jin; Wu, Yi-Jin; et al. (ACS applied materials & interfaces, 2023)
The cathodic product Li2CO3, due to its high decomposition potential, has hindered the practical application of rechargeable Li-CO2/O2 batteries. To overcome this bottleneck, a Pt/FeNC cathodic catalyst is fabricated by dispersing Pt nanoparticles (NPs) with a uniform size of 2.4 nm and 8.3 wt % loading amount into a porous microcube FeNC support for high-performance rechargeable Li-CO2/O2 batteries. The FeNC matrix is composed of numerous two-dimensional (2D) carbon nanosheets, which is derived from an Fe-doping zinc metal–organic framework (Zn-MOF). Importantly, using Pt/FeNC as the cathodic catalyst, the Li-CO2/O2 (V CO2 /V O2 = 4:1) battery displays the lowest overpotential of 0.54 V and a long-term stability of 142 cycles, which is superior to batteries with FeNC (1.67 V, 47 cycles) and NC (1.87 V, 23 cycles) catalysts. The FeNC matrix and Pt NPs can exert a synergetic effect to decrease the decomposition potential of Li2CO3 and thus enhance the battery performance. In situ Fourier transform infrared (FTIR) spectroscopy further confirms that Li2CO3 can be completely decomposed under a low potential of 3.3 V using the Pt/FeNC catalyst. Impressively, Li2CO3 exhibits a film structure on the surface of the Pt/FeNC catalysts by scanning electron microscopy (SEM), and its size can be limited by the confined space between the carbon sheets in Pt/FeNC, which enlarges the better contacting interface. In addition, density functional theory (DFT) calculations reveal that the Pt and FeNC catalysts show a higher adsorption energy for Li2CO3 and Li2CO4 intermediates compared to the NC catalyst, and the possible discharge pathways are deeply investigated. The synergetic effect between the FeNC support and Pt active sites makes the Li-CO2/O2 battery achieve optimal performance.